Significant Loss of Skeletal Muscle Mass Occurs After High-Energy Trauma in Young Adults. (14th June 2022) - Davison, John; Miller, Aspen; Leary, Steven; Glass, Natalie; Wilken, Jason; Reider, Lisa; Marsh, J Lawrence; Willey, Michael; Grossmann, Ruth
Abstract: Objectives: Significant loss of skeletal muscle mass occurs early after high-energy trauma, leading directly to prolonged functional limitations. As we investigate nutrition interventions to reduce loss of muscle mass, we need to quantify changes in muscle mass after these devastating injuries. The aim of this study was to characterize baseline nutrition and changes in muscle mass after high-energy trauma in a young adult population. Methods: We enrolled patients 18–55 years old indicated for operative fixation of either, an open pelvic or extremity fracture, or ≥2 pelvic and/or extremity fractures due to a high-energy mechanism. Baseline assessment of body composition (Lean Body Mass [LBM], Skeletal Muscle Mass [SMM]), was measured within 72 hours of admission using bioelectrical impedance and repeated 6 weeks after injury. Results are reported as median (IQR). Changes in LBM and SMM were evaluated using Wilcoxon Signed Rank tests. Sarcopenia was defined by gender-specific cutoffs for appendicular skeletal mass index. Dietary intake was evaluated using food frequency questionnaires. Inadequate protein intake was classified using the Estimated Average Requirement cut-point method, while inadequate caloric intake was defined as intake below basal metabolic rate. Results: Sixteen subjects (14 male) age 38.4 ± 9.6 years were enrolled. At baseline, 3 reported inadequate protein intake and 5 reported inadequate caloric intake. Six weeks after injury participants experienced significant losses in LBM (−4.5kg (−8.8 to −1.4), P = 0.019) and SMM (−3.1kg (−5.6 to −0.3), P = 0.043). The injured extremity had significantly greater loss of LBM compared to the uninjured extremity (−4.0 (−17.1–3.5), P = 0.0495). Five were baseline sarcopenic, with one additional participant meeting the criteria by 6 weeks. Baseline protein and calorie deficiency was not significantly associated with muscle loss. Conclusions: This study documented devastating loss of lean body mass and skeletal muscle mass after high-energy trauma in young adults. These losses are likely a combination of immobilization and catabolic response for wound and fracture healing. Understanding loss of muscle mass after injury is important to design impactful rehabilitative and nutrition interventions in this complicated patient population. Funding Sources: None.